FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN BUSANA PADA MAHASISWI MALUKU TENGGARA DI YOGYAKARTA - Selvisina Salawaney; Endang Wani Karyaningsih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The objectives of this research are to know the factors influencing the selection of dress base on: 1) internal factors: personality and knowledge, 2) external factors: communication and social environment. The type of the research is descriptive quantitative. Samples are taken by proportional random sampling. Data are collected by questinaire and documentation. The results show:  the factors influencing the selection of dress are categorized high by relative frequency 74.19%, meaning that good dress performance determines personality of someone. The selection of dress is influenced by two factors, that is, internal and external factors, 2) the large influent factor to the dress selection can be seen from each indicator category. The internal factors cover personality indicator (25.34%) and knowledge (26.67%). External indicator factors of communication environment (21.20%), social environment (26.79). It explains that  social environment factor gives the highest contribution.